What agricultural practices are most likely to deliver ‘sustainable intensification’ in the UK? - Dicks, L.V.; Rose, D.C.; Ang, F.; Aston, S.; Birch, A.N.E.; Boatman, N.; Bowles, L.; Chadwick, D.; Dinsdale, A.; Durham, S.; Elliott, J.; Firbank, L.; et al. (Wiley Open Access, 2018)
Sustainable intensification is a process by which agricultural productivity is enhanced whilst also creating environmental and social benefits. We aimed to identify practices likely to deliver sustainable intensification, currently available for UK farms but not yet widely adopted. We compiled a list of 18 farm management practices with the greatest potential to deliver sustainable intensification in the UK, following a well-developed stepwise methodology for identifying priority solutions, using a group decision-making technique with key agricultural experts. The list of priority management practices can provide the focal point of efforts to achieve sustainable intensification of agriculture, as the UK develops post-Brexit agricultural policy, and pursues the second Sustainable Development Goal, which aims to end hunger and promote sustainable agriculture. The practices largely reflect a technological, production-focused view of sustainable intensification, including for example, precision farming and animal health diagnostics, with less emphasis on the social and environmental aspects of sustainability. However, they do reflect an integrated approach to farming, covering many different aspects, from business organization and planning, to soil and crop management, to landscape and nature conservation. For a subset of ten of the priority practices, we gathered data on the level of existing uptake in English and Welsh farms through a stratified survey in seven focal regions. We find substantial existing uptake of most of the priority practices, indicating that UK farming is an innovative sector. The data identify two specific practices for which uptake is relatively low, but which some UK farmers find appealing and would consider adopting. These practices are: prediction of pest and disease outbreaks, especially for livestock farms; staff training on environmental issues, especially on arable farms.